ANALYSIS OF THE APPLICATION OF CRIMINAL REGULATIONS AGAINS NATURAL RESOURCE MANAGERS FOR ENVIRONMENTAL VIOLATIONS - Elyssa, Bening (Communale Journal, 2025)
Violations in natural resource management often occur and result in significant negative impacts on the environment, threaten the sustainability of ecosystems, and cause social and economic losses. By focusing on the Indonesian legal framework, this study aims to determine the extent of the effectiveness of the application of criminal sanctions against natural resource managers who commit environmental violations and the effectiveness of criminal law in dealing with environmental damage caused by poor management of natural resources. This research uses a normative juridical method, which focuses on the analysis of relevant legal regulations and doctrines. The findings show that, despite the various legal provisions governing criminal sanctions, their application is often inconsistent and ineffective. Several factors include weak supervision, low public awareness, limited resources for law enforcement. This study recommends the need for improvements in the law enforcement system, capacity building for law enforcement agencies, and strengthening community participation in monitoring natural resource management to encourage greater accountability for environmental protection